2022
DOI: 10.1007/s43217-022-00112-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil loss rate using GIS–RUSLE interface in Tashat Watershed, Northwestern Ethiopia

Abstract: The erosion of soil is one of the most difficult and ongoing problems caused by deforestation, improper cultivation, uncontrolled grazing, and other anthropogenic activities. As a result, assessing the level and quantity of soil erosion is essential for agricultural productivity and natural resource management. Thus, the goal of this study was to quantify soil loss rates and identify hotspot locations in the Tashat watershed, Abay basin, Ethiopia. Thematic factor maps, comprising rainfall erosivity factor (R),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, different erosion rates in the Rift Valley Basin have been recorded. Degife et al (2021) discovered 37 t/ha/year in the Lake Hawassa watershed, and Jothimani et al (2022) estimated 68 t/ha/year in the Weito watershed, Woldesenbet et al (2020) found 30.5 t/ha/year in Meki river watershed, Meshesha et al (2012) reported 56 t/ha/year in Central Rift Valley, Wolka et al (2015) found 45 t/ha/year in the central rift valley, Abebe (2015) reported 68.7 t/ha/year in the Cheraqe Watershed Bilate Sub Basin, Mengie et al (2022) investigated 64.2 t/ha/year in Tashat Watershed, Northwestern Ethiopia, Negese et al (2021) found 38.7 t/ha year for Chereti Watershed, Northeastern Ethiopia, and Elnashar et al (2021) estimated 39.7 t/ha/year for the Blue Nile Basin.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, different erosion rates in the Rift Valley Basin have been recorded. Degife et al (2021) discovered 37 t/ha/year in the Lake Hawassa watershed, and Jothimani et al (2022) estimated 68 t/ha/year in the Weito watershed, Woldesenbet et al (2020) found 30.5 t/ha/year in Meki river watershed, Meshesha et al (2012) reported 56 t/ha/year in Central Rift Valley, Wolka et al (2015) found 45 t/ha/year in the central rift valley, Abebe (2015) reported 68.7 t/ha/year in the Cheraqe Watershed Bilate Sub Basin, Mengie et al (2022) investigated 64.2 t/ha/year in Tashat Watershed, Northwestern Ethiopia, Negese et al (2021) found 38.7 t/ha year for Chereti Watershed, Northeastern Ethiopia, and Elnashar et al (2021) estimated 39.7 t/ha/year for the Blue Nile Basin.…”
Section: Resultsmentioning
confidence: 99%
“…For this investigation, the R factor was estimated using average annual precipitation data for the 21 years from 1990 to 2021. Equation (2) [3,33] was used to estimate the relationship between yearly precipitation and the R factor.…”
Section: Rainfall-runof Erosivity Factor (R)mentioning
confidence: 99%
“…Te Revised Universal Soil Loss Equation (RUSLE), established by [33], is widely utilized as an empirical method for calculating soil loss, specifcally in rill and inter-rill erosion situations. Te RUSLE model distinguishes itself from others due to its simplicity, adaptability, cost-efectiveness, and efciency.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this difficulty, several models and techniques have been developed to simplify SE modelling and better our knowledge of the pattern and processes of SE. Previous researchers have found that RUSLE model outperformed other models in terms of accuracy and simplicity to estimate the potential soil erosion (Mengie at al., 2022;Somasiri et al, 2022). Therefore, in the present study, we used the RUSLE model to estimate the potential soil erosion for current and future scenarios.…”
Section: Introductionmentioning
confidence: 99%